Interaksionisme Simbolik Perempuan Muslim dalam ‘Aksi Gejayan Memanggil’ - Siti Nuralfia Abdullah (JURNAL ILMIAH SYI'AR, 2019)
This study analyzes the symbolic interaction of Herbert Mead to discourse the actions of muslim women in ‘Aksi Gejayan Memanggil’ on in order to voice opinions of rejection of problematic revisions to the law. Symbolic interaction as a form of muslim women's communication role is carried out to influence the government in order to be able to accept all forms of demands. The purpose of this study is to analyze the symbolic interaction of muslim women to realize community support in voicing opinions. Through descriptive qualitative methods, by understanding data taken from social media as well as several related books resulting in symbolic interactions that are shown by women is to build a positive outlook in the call to action, these actions are positive actions as an effort to defend and reject their revisions to the law namely changes to the RKUHP, the elimination of sexual violence, and several other demands. Moreover, this action is a form of the presence or existence of women in defense of their rights and obligations